Does the Covid-19 Outbreak Impacts On Economic Growth? An Evidence from Indonesia - Aprina, Hilda; Majid, M. Sabri Abd.; Silvia, Vivi (iora, 2021)
This study aims to analyze the effectS of the COVID-19 pandemic, labor, domestic direct investment (DDI), AND foreign direct investment (FDI) on economic growth in Indonesia. The type of data used in this study is panel data, which is a combination of cross-section and THE time series data (Silvia, 2020). The cross-section data involves 34 provinces and time-series data covers the period from the first quarter of 2018 to the second quarter of 2021. The result found out that the regression coefficient of labor has a positive and significant effect at the 5 percent level, which means that if the number of workers increases by 1 percent, economic growth will increase by 0.03 percent. Furthermore, the FDI variable also has a significant and positive effect on economic growth in Indonesia. We can see in table 3.2 that the FDI variable is significant at the 5 percent level with a regression coefficient of 0.012, this means that an increase in FDI by 1 percent will accelerate economic growth by 0.012 percent. From the results of data processing obtained by the author, it can be seen that the DDI variable has a positive but not significant effect on economic growth in Indonesia, this can be seen from the p-value which is greater than 5 percent. The regression coefficient of -0.001 proves that the COVID-19 pandemic has a negative impact on economic growth in Indonesia. When the COVID-19 pandemic reached the territory of Indonesia, economic growth slowed by 0.001 percent.